Chemoselective Coatings of GL13K Antimicrobial Peptides for Dental Implants - Isha Mutreja; Caixia Lan; Qishun Li; Conrado Aparicio (MDPI AG, 2023)
Dental implant−associated infection is a clinical challenge which poses a significant healthcare and socio−economic burden. To overcome this issue, developing antimicrobial surfaces, including antimicrobial peptide coatings, has gained great attention. Different physical and chemical routes have been used to obtain these biofunctional coatings, which in turn might have a direct influence on their bioactivity and functionality. In this study, we present a silane−based, fast, and efficient chemoselective conjugation of antimicrobial peptides (Cys−GL13K) to coat titanium implant surfaces. Comprehensive surface analysis was performed to confirm the surface functionalization of as−prepared and mechanically challenged coatings. The antibacterial potency of the evaluated surfaces was confirmed against both Streptococcus gordonii and Streptococcus mutans, the primary colonizers and pathogens of dental surfaces, as demonstrated by reduced bacteria viability. Additionally, human dental pulp stem cells demonstrated long−term viability when cultured on Cys−GL13K−grafted titanium surfaces. Cell functionality and antimicrobial capability against multi−species need to be studied further; however, our results confirmed that the proposed chemistry for chemoselective peptide anchoring is a valid alternative to traditional site−unspecific anchoring methods and offers opportunities to modify varying biomaterial surfaces to form potent bioactive coatings with multiple functionalities to prevent infection.